Sosialisasi dan Workshop Digital Marketing untuk Peningkatan Kualitas UMKM yang Unggul di Desa Timbang Kabupaten Kuningan - Mali Amilusholihah; rizki indrawan; Marisa Wijayanti (CV. Armas Suan Sejahtera, 2025)
This community service activity was carried out with the aim of improving the understanding and capabilities of Micro, Small, and Medium Enterprises (MSMEs) in Timbang Village, Kuningan Regency, in utilizing digital media as a tool to market their products. The rapid development of information technology requires business actors, including those in rural areas, to adapt to digital marketing strategies in order to maintain competitiveness. The implementation methods include socialization and interactive discussions on the basics of digital marketing, the use of Instagram social media, as well as techniques for creating engaging promotional content. The results of the activity showed a high level of enthusiasm from participants, as indicated by their active involvement in question-and-answer sessions and their willingness to apply the material provided. This activity has proven to have a positive impact on increasing participants’ digital literacy and has opened new insights regarding modern marketing strategies. Therefore, similar activities are highly relevant to be continued regularly in order to encourage MSME empowerment through strengthening digital capacity.